New amphiphilic glycopolymers by click functionalization of random copolymers – application to the colloidal stabilisation of polymer nanoparticles and their interaction with concanavalin A lectin - Otman, Otman; Boullanger, Paul; Drockenmuller, Eric; Hamaide, Thierry (Beilstein Journal of Organic Chemistry, 2010)
Glycopolymers with mannose units were readily prepared by click chemistry of an azido mannopyranoside derivative and a poly(propargyl acrylate-co-N-vinyl pyrrolidone). These glycopolymers were used as polymer surfactants, in order to obtain glycosylated polycaprolactone nanoparticles. Optimum stabilization for long time storage was achieved by using a mixture of glycopolymers and the non-ionic triblock copolymer Pluronic® F-68. The mannose moieties are accessible at the surface of nanoparticles and available for molecular recognition by concanavalin A lectin. Interaction of mannose units with the lectin were evaluated by measuring the changes in nanoparticles size by dynamic light scattering in dilute media.
Keywords: click chemistry; con A lectin; dynamic light scattering; glycopolymer; polymer nanoparticles

(untitled) - Muraji, Y.; Nakagawa, Y.; Yamane, S.; Kawanami, S.; Aoki, T.; Saito, S.; Ikai, A. (Jpn. J. Appl. Phys., 2006)

(untitled) - Galea, I.; Palin, K.; Newman, T. A.; Van Rooijen, N.; Perry, H. V.; Boche, D. (Glia, 2005)

(untitled) - Okada, M. (Prog. Polym. Sci., 2001)

(untitled) - Hamaide, T.; Pantiru, M.; Fessi, H.; Boullanger, P. (Macromol. Rapid Commun., 2001)

(untitled) - Racles, C.; Hamaide, T. (Macromol. Chem. Phys., 2005)

(untitled) - Berson, S.; Halila, S.; Driguez, H.; Viet, D.; Fleury, E.; Hamaide, T. (Macromol. Chem. Phys., 2008)

(untitled) - Yamada, K.; Minoda, M.; Miyamoto, T. (Macromolecules, 1999)

(untitled) - Ladmiral, V.; Mantovani, G.; Clarkson, G. J.; Cauet, S.; Irwin, J. L.; Haddleton, D. M. (J. Am. Chem. Soc., 2006)

(untitled) - Geng, J.; Mantovani, G.; Tao, L.; Nicolas, J.; Chen, G.; Wallis, R.; Mitchell, D. A.; Johnson, B. R. G.; Evans, S. D.; Haddleton, D. M. (J. Am. Chem. Soc., 2007)

(untitled) - Cade, D.; Ramus, E.; Rinaudo, M.; Auzely-Velty, R.; Delair, T.; Hamaide, T. (Biomacromolecules, 2004)

(untitled) - Satoh, A.; Kojima, K.; Koyama, K.; Ogawa, H.; Matsumoto, I. (Anal. Biochem., 1998)

(untitled) - Otman, O.; Boullanger, P.; Lafont, D.; Hamaide, T. (Macromol. Chem. Phys., 2008)

(untitled) - Damiron, D.; Desorme, M.; Ostaci, R. V.; El Akhrass, S.; Hamaide, T.; Drockenmuller, E. (J. Polym. Sci., Part A: Polym. Chem., 2009)

(untitled) - Veron, L.; Revol, M.; Mandrand, B.; Delair, T. (J. Appl. Polym. Sci., 2001)

(untitled) - Iojoiu, C.; Cade, D.; Fessi, H.; Hamaide, T. (Polym. Int., 2005)

(untitled) - Wilhelm, F.; Chatterjee, S. K.; Rattay, B.; Nuhn, P.; Benecke, R.; Ortwein, J. (Liebigs Ann., 1995)

Methods in Carbohydrate Chemistry - Thompson, A.; Wolfrom, M. L. (Academic Press, Inc., 1963)

(untitled) - Summerlin, B. S.; Tsarevsky, N. V.; Louche, G.; Lee, R. Y.; Matyjaszewski, K. (Macromolecules, 2005)

(untitled) - Mammen, M.; Choi, S. K.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Lundquist, J. J.; Toone, E. J. (Chem. Rev., 2002)

(untitled) - Goldstein, I. J.; Hayes, C. E. (Adv. Carbohydr. Chem. Biochem., 1978)

(untitled) - Kitano, H.; Kawabata, J.; Muramoto, T. (Macromol. Chem. Phys., 1996)

(untitled) - Kanellopoulos, P. N.; Pavlou, K.; Perrakis, A.; Agianian, B.; Vorgias, C. E.; Mavrommatis, C.; Soufi, M.; Tucker, P. A.; Hamodrakas, S. J. (J. Struct. Biol., 1996)

(untitled) - Quintanar-Guerrero, D.; Allemann, E.; Doelker, E.; Fessi, H. (Colloid Polym. Sci., 1997)

(untitled) - Quintanar-Guerrero, D.; Allemann, E.; Doelker, E.; Fessi, H. (Pharm. Res., 1998)